Evaluating the microbicidal, antiparasitic and antitumor effects of CR-LAAO from Calloselasma rhodostoma venom - Costa, Tássia R.; Menaldo, Danilo L.; Silva, Cássio Prinholato da; Sorrechia, Rodrigo [UNESP]; Albuquerque, Sérgio de; Pietro, Rosemeire C. L. R. [UNESP]; Ghisla, Sandro; Antunes, Lusânia M Greggi; Sampaio, Suely V. (Elsevier B. V., 2015)
CR-LAAO is an l-amino acid oxidase from Calloselasma rhodostoma snake venom that has been broadly studied regarding its structural and biochemical characteristics, however, few studies have investigated its pharmacological effects. The present study aimed at the evaluation of the biotechnological potential of CR-LAAO by determining its bactericidal, antifungal, leishmanicidal and trypanocidal activity, as well as its cytotoxicity on human tumor and non-tumor cell lines. After 24h of preincubation, CR-LAAO showed bactericidal effects against both Staphylococcus aureus (MIC 0.78μg/mL) and Escherichia coli (MIC 31.25μg/mL) strains, inducing dismantle of bacterial cell walls. After 6h of preincubation with Candida albicans, CR-LAAO was able to inhibit 80% of the yeast growth, and it also showed cytotoxic activity on Leishmania species and Trypanosoma cruzi. Additionally, CR-LAAO showed high cytotoxicity on HepG2 and HL-60 tumor cells (IC50 10.78 and 1.7μg/mL), with lower effects on human mononuclear cells (PBMC). The cytotoxic effects of CR-LAAO were significantly inhibited in the presence of catalase, which suggests the involvement of hydrogen peroxide in its mechanisms of toxicity. Therefore, CR-LAAO showed promising pharmacological effects, and these results provide important information for the development of therapeutic strategies with directed action, such as more effective antimicrobial agents.
Keywords: Calloselasma rhodostoma; Pharmacological evaluation; L-amino acid oxidase